Factors associated with longer hospital admission in elderly patients with major neurocognitive disorder - Tarina Steenkamp; Paslius S. Mazibuko; Carla Kotzé (South African Journal of Psychiatry, 2023)
Background: Major neurocognitive disorder presents many challenges to patients, families and healthcare systems, especially when a patient requires admission to a psychiatric hospital.